Development of Ancient Khmer Stone Castle Ontology - Chansanam, Wirapong; Li, Chunqiu (Journal of Ecohumanism, 2024)
This research delves into the development of ontology, a crucial aspect of knowledge organization system studies. The primary goal is to establish a semantic search system tailored to the Khmer stone castles of the Greater Mekong Subregion (GMS), specifically addressing the challenge of semantic gaps. This paper details a novel approach to developing ontologies for Khmer stone castles in the GMS to enhance our understanding of these countries’ rich and ancient cultural heritage. A systematic four-step theoretical framework for ontology development was adopted, utilizing the Hozo Ontology Editor to create the ontologies by used the Wizard for documenting ontologies (WIDOCO) framework for web ontology platform. This methodology plays a key role in differentiating relevant from irrelevant data, thus significantly improving the efficiency of semantic searches. Central to this study is developing a comprehensive ontology encompassing ten primary classes: castle, location, country, Khmer art, art type, castle size, castle type, material, religion, and condition. This ontology is foundational for developing a semantic search system designed explicitly for the Khmer stone castles in the GMS. The insights from this research offer significant implications for advancing semantic search systems in cultural heritage, providing a robust framework for future studies in this field.